Optical coherence tomography angiography for longitudinal monitoring of vascular changes in human cutaneous burns. Issue 9 (13th July 2016) - Gong, Peijun; Es'haghian, Shaghayegh; Wood, Fiona M.; Sampson, David D.; McLaughlin, Robert A.
Abstract: Assessment of vasculature is an important aspect of monitoring healing of cutaneous burn injuries. Recent advances in optical coherence tomography (OCT) have enabled it to be used to perform high‐resolution imaging of the cutaneous vasculature in vivo, with the potential to provide a superior alternative to the conventional assessment of scoring skin color. The goal of this study is to investigate the feasibility of OCT angiography for longitudinal monitoring of vasculature and identification of vascular features in human cutaneous burns. We integrate several OCT imaging protocols and image‐processing techniques into a systematic method for longitudinal monitoring and automatic quantification. The demonstration of this method on a partial‐thickness burn shows the accurate co‐location of longitudinal scans; characteristic vascular features in different healing phases; and eventual decrease of the elevated vasculature area density and vessel diameter to normal levels. Such a method holds promise for longitudinal monitoring of vasculature in burn injures as well as in other cutaneous vascular pathologies and responses to treatment.